2003
DOI: 10.1088/0031-9155/48/13/307
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy imaging in full-field digital mammography: a phantom study

Abstract: A dual-energy technique which employs the basis decomposition method is being investigated for application to digital mammography. A three-component phantom, made up of plexiglas, polyethylene, and water, was doubly exposed with the full-field digital mammography system manufactured by General Electric. The 'low' and 'high' energy images were recorded with a Mo/Mo anode-filter combination and a Rh/Rh combination, respectively. The total dose was kept within the acceptable levels of conventional mammography. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 22 publications
1
43
0
1
Order By: Relevance
“…In 1985, Johns et al [4] , using a scanned projection radiography system and a phantom containing breast tissue samples, have shown that DE could increase the detectability of calcium deposits. More recent studies have been performed with commercial digital units.…”
Section: A Study On Dual-energy Subtraction In Digital Mammographymentioning
confidence: 99%
“…In 1985, Johns et al [4] , using a scanned projection radiography system and a phantom containing breast tissue samples, have shown that DE could increase the detectability of calcium deposits. More recent studies have been performed with commercial digital units.…”
Section: A Study On Dual-energy Subtraction In Digital Mammographymentioning
confidence: 99%
“…The breast thickness estimation is limited by the assumptions required in the breast shape model and the errors associated with the paddle thickness measurement (Ducote and Molloi 2010a). Dual-energy imaging has previously been used in contrast-imaging and calcification imaging , Marziani et al 2002, Taibi et al 2003, Kappadath and Shaw 2005, Lemacks et al 2002. Recently, studies have reported the use of these techniques in the quantification of breast density and the estimation of the glandular and adipose thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous dual energy mammography techniques have primarily focused on imaging calcium, [13][14][15][16][17][18][19][20][21] iodine, and neoplastic breast tissue. [26][27][28][29] The adipose and glandular tissues have effective atomic numbers of 6.33 and 6.93, respectively. 30 Dual energy mammography can exploit this effective atomic number difference to quantify glandular and adipose tissue thicknesses for breast density measurement.…”
Section: Introductionmentioning
confidence: 99%